The Characterization of Indonesian's Natural Zeolite For Water Filtration System - Mirzan T. Razzak; Thamzil Las; Priyambodo Priyambodo (Jurnal Kimia Valensi, 2013)
AbstractThe characterization of Indonesian's natural zeolite for water purification has been done. The objective is to obtain a general guidance for development of natural zeolite in molecular sieves, ion exchange and catalyst applications. The zeolites originated frol Lampung (ZL) was characterized by using XRD. It was found that the zeolites indicate belong to clinoptilatite and mordenite groups, respectively. The crystal system for ZL was monoclinic with end-centered lattice and space group of Cm/2 (12). The crystal system for ZB was orthorhombic with end-centered lattice and space group of CmC21 (36). The character of both zeolites were confirm by ICDD standard library. It was also found that the particle size of zeolites did not affect the XRD spectra where zeolite of 40-50 mesh was similar to that XRD spectra of zeolite of 170-200 mesh. The chemical analyses show that both zeolites contain almost similar chemical elements. The contents of Fe, Ca, and K were found higher in ZL as it is compared to ZB. Reciprocally, Na was Pb and Fe elements. These ability were improved by chemical activation of zeolites. These two elements probably were originally exist in the zeolite structure. These characterization is necessary to designing a further development of natural zeolite applications.Keywords : natural zeolite, clinoptilolite, mordenite, x-ray diffraction, water filter